The new rice varieties Virasan and Piruet - P. I. Kostylev; E. V. Krasnova (Аграрная наука Евро-Северо-Востока, 2018)
The article provides the results of breeding work fulfilled by the FSB SI Agricultural Research Center “Donskoy”, in the course of which the new productive varieties Virasan and Pimet well adapted to the climate and soil of the south of the Rostov Region were successfully developed and handed over for the State Variety Testing. The early ripening rice variety Virasan was developed from the hybridization of the early ripening variety Virazh and the average ripening, energetically growing variety Kuban 3. The vegetation period of the variety is 110 days. The plants are of low height (76 cm). The compact erected panicles are 14 cm of height with 112 kernels of 7.5 mm length and 4.0 mm width on average. 1000 kernels weight is 31.4 g. In the competitive testing, the average productivity of Virasan during 3 years was 6.66 t/ha, which is 0.50 t/ha more than the standard variety Kontakt. The medium-ripening variety Pimet is developed from the crossing of the hybrids C101-A-51« Boyarin and C101-Lac x Virage. With the help of marker selection, it was possible to obtain forms having three blast resistant genes Pi-1, Pi-2, Pi-33 in the homozygous state. The vegetation period from sowing to maturation is 124 days. The variety is of medium height with 88 cm. A panicle of 17.5 cm length forms 162 oval kernels of 8.9 mm length and 3.7 mm width on average. 1000 kernels weight is 31.6 g on average. The productivity of the variety ‘Pimet’ was 9.57 t/ha in the competitive variety testing on average, which exceeded productivity of the standard variety Yuzhanin by 1.13 t/ha.